Insects as source of phenolic and antioxidant entomochemicals in the food industry - Torres-Castillo, Jorge A.; Olazarán-Santibáñez, Fabián E. (Frontiers in Nutrition, 2023)
Edible insects are a natural resource with profound interest in the food industry. Not only because of their nutritional content and technical production advantage, but also for the presence of bioactive compounds known as entomochemicals. These include phenolic, alkaloid, and terpenoid compounds, as well as aminoacids derivatives, among others. The phenolic compounds have been the best characterized due to their role in food development and bioactive properties. The major taxonomic orders studied in this regard include Orthoptera, Coleoptera, and Lepidoptera, whose edible specimens have antioxidant effects provided by the phenolic compounds contained therein. The use of these insects in the development of nutritious foods will enhance the number of options available for the human population. However, depth research is still needed to guarantee the aforementioned bioactivity in processed foods and ensure its innocuity, thus minimizing the risk of allergic reactions and allowing the full utilization of edible insect species in the food industry.